IMPLEMENTATION OF COOPERATIVE LEARNING METHOD GALLERY WALK IN IMPROVING STUDENTS' SCIENCE LEARNING OUTCOMES IN MUHAMMADIYAH KAMPUNG BHARU MALAYSIA GUIDELINES - Azlinda, Nur; Syamsuyurnita, Syamsuyurnita; Sari, Suci Perwita; Nasution, Ismail Saleh (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study was to determine the Implementation of the Gallery Walk Cooperative Learning Method in Improving Student Science Learning Outcomes at the Muhammadiyah Guidance Center in Kampung Bharu Malaysia. This research is a qualitative research. This research was carried out by the Muhammadiyah Guidance Center in Kampung Bharu Malaysia. The types and sources of data are in the form of Primary data and Secondary data. Primary data obtained directly through interviews. Secondary data is research supporting data such as documents, activity results reports, through words and actions from research informants and research subjects related to the Implementation of the Gallery Walk Cooperative Learning Method in Improving Student Science Learning Outcomes. Data collection techniques in this study are through observation, interviews, and documentation. The results of this study indicate that there are several things that are done by science teachers in implementing the Gallery Walk Cooperative Learning Method in Improving Student Science Learning Outcomes at the Muhammadiyah Guidance Studio Kampung Bharu Malaysia, namely implementing planning before carrying out science learning using the Gallery Walk method for students in the Studio Guidance of Muhammadiyah Kampung Bharu Malaysia. Furthermore, the implementation of the Gallery Walk method is going well, this is evidenced by the smooth science learning activities carried out in class. And the evaluation of the application of the Gallery Walk method in learning science has gone smoothly because it is in accordance with the planning and implementation